2022
DOI: 10.1101/2022.02.10.480009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Binding Interactions between RBD of Spike-Protein and Human ACE2 in Omicron variant

Abstract: Emergence of new SARS-CoV-2 Omicron VOC (OV) has exacerbated the COVID-19 pandemic due to a large number of mutations in the spike-protein, particularly in the receptor-binding domain (RBD), resulting in highly contagious and/or vaccine-resistant strain. Herein, we present a systematic analysis based on detailed molecular dynamics (MD) simulations in order to understand how the OV RBD mutations affect the ACE2 binding. We show that the OV RBD binds to ACE2 more efficiently and tightly due predominantly to stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…However, this computational tool gives comparably low binding energies of peptide-protein docking due to the molecular size, high flexibility, and complexing conformation of the peptide ligand, in addition to the simplification of the analysis of ADV (the electrostatic and solvation potentials are neglected, while van der Waals potential, the nondirectional hydrogen bond term, the hydrophobic term, and a conformational entropy penalty are considered) [20,21]. It can be observed that the binding energy values (Table 1 and Table 2) are significantly lower than the binding energies reported in similar works [6,60,61]. For instance, the experimental and theoretical values of the binding energy reported for ACE2-RBD is around −12.0 kcal/mol, which is higher than the binding energy of −4.6 kcal/mol given here [61].…”
Section: Binding Energy By Protein Binding Energy Predictionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, this computational tool gives comparably low binding energies of peptide-protein docking due to the molecular size, high flexibility, and complexing conformation of the peptide ligand, in addition to the simplification of the analysis of ADV (the electrostatic and solvation potentials are neglected, while van der Waals potential, the nondirectional hydrogen bond term, the hydrophobic term, and a conformational entropy penalty are considered) [20,21]. It can be observed that the binding energy values (Table 1 and Table 2) are significantly lower than the binding energies reported in similar works [6,60,61]. For instance, the experimental and theoretical values of the binding energy reported for ACE2-RBD is around −12.0 kcal/mol, which is higher than the binding energy of −4.6 kcal/mol given here [61].…”
Section: Binding Energy By Protein Binding Energy Predictionmentioning
confidence: 87%
“…For instance, the experimental and theoretical values of the binding energy reported for ACE2-RBD is around −12.0 kcal/mol, which is higher than the binding energy of −4.6 kcal/mol given here [61]. Therefore, the PRODIGY web server was used to estimate the binding energy for peptide-RBD docking, since it has been demonstrated that PRODIGY can produce results comparable with those obtained experimentally and most standard in silico analyses [38][39][40]60].…”
Section: Binding Energy By Protein Binding Energy Predictionmentioning
confidence: 96%
“…For example, relative to WT, the net positive charge on each RBD increases by two and three for Delta and Omicron variants, respectively. This increase in charge is accompanied both by higher infection rate and reduced potency of neutralizing antibodies [4][5][6][7][8][9][10][11][12]. Both effects are consistent with evolutionary pressure toward RBD mutations which increase positive charge: Firstly, as hACE2 is a charge negative entity [13] thus the electrostatic interaction is increased; and secondly, the electrostatic surfaces of neutralizing antibodies reveal that most antibodies have positively charged RBD-recognition domains.…”
Section: Introductionmentioning
confidence: 83%
“…In this case, it formed an additional salt bridge with Asp38. Interactions with Tyr41 and Gln42 of ACE-2 were stronger compared to WT spike interaction [25].…”
Section: Details About Mutational Effect On the Rbd-ace2 Interactionsmentioning
confidence: 89%
“…Spike variants with mutations like N440K and G476S are high a nity ACE-2 binders and are located in solvent accessible loop regions. Compared to WT spike, both mutations lead to drastic conformational alterations wherein, it reorients the RBM loop towards the binding interface thereby allowing additional interactions [25,26]. Deleterious mutations like G446S and Y505H were also high a nity binders to ACE-2 but was found to be destabilizing for RBD [25,27].…”
Section: Details About Mutational Effect On the Rbd-ace2 Interactionsmentioning
confidence: 99%